Effectiveness of Sharia Letter of Credit (L/C) as an International Trade Finance Instrument in Islamic Banks - Riki Maulana; Reynaldi Gusti Ananda (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2026)
Despite the growing adoption of Sharia-compliant trade finance instruments, empirical and conceptual assessments of the effectiveness of Sharia Letter of Credit (L/C) in international trade remain limited, particularly in the context of Islamic banking in emerging markets. Existing studies predominantly focus on normative compliance or contract structures, leaving a gap in evaluating operational effectiveness and regulatory alignment. This study addresses this gap by examining the effectiveness of Sharia L/C as an international trade financing instrument in Islamic banks. Employing a qualitative normative–empirical methodology, the research analyzes DSN-MUI fatwas, regulatory frameworks, and operational practices of Sharia L/Cs through document analysis and secondary empirical data. The findings reveal that Sharia L/Cs effectively enhance payment security, risk mitigation, and Sharia compliance through the integration of contracts such as wakālah, qard, and hiwālah. However, effectiveness is constrained by operational complexity, limited standardization, and inconsistencies between fatwa provisions and banking implementation. The study’s novelty lies in its integrated evaluation of Sharia compliance, operational performance, and regulatory coherence, offering a comprehensive framework to strengthen the role of Sharia L/Cs in global Islamic trade finance.